STUDI KRITIS PENGEMBANGAN KOMPETENSI APARATUR SIPIL NEGARA PEMERINTAH KOTA TANGERANG MELALUI IMPLEMENTASI SISTEM TANGERANG GOVERNMENT UNIVERSITY - Abidin, Zainal (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2024)
The global Covid-19 pandemic from 2020 to 2022 hindered civil servants’ competency development progress. To address this, Tangerang City Government has established an integrated competency development system called Government University (Gorvu) at the end of 2023. This mini-research aims to assess the service conditions, perceptions, and expectations of Civil Servants regarding regarding competency development facilitated by the Tangerang Gorvu e-learning platform. A qualitative descriptive approach was used to analyze the business process management of the Tangerang Gorvu system. Data sources include secondary data from the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) and primary data from 43 respondents who attended on-the-spot training at Graha Bhakti Karya. Research tools comprised interviews with 3 key individuals and a Google Forms questionnaire. Data analysis employed systematic literature review techniques for secondary data, while primary data was analyzed using statistical tabulation displayed in charts and graphs. Findings reveal that employees generally recognize the competency development provided through the Tangerang Gorvu system, though many do not yet fully understand its usage procedures. The main challenges in implementing the Gorvu digital platform include smartphone usage difficulties and low adaptability among many civil servants. Moreover, employees feel that the current selection of learning videos on the platform is limited; preferred video types are, in order, those on functional roles, success stories from other regions, technical training, examples of ASN BerAKHLAK, and government managerial skills..